2019
DOI: 10.1098/rsos.181803
|View full text |Cite
|
Sign up to set email alerts
|

Interacting stressors matter: diet quality and virus infection in honeybee health

Abstract: Honeybee population declines have been linked to multiple stressors, including reduced diet diversity and increased exposure to understudied viral pathogens. Despite interest in these factors, few experimental studies have explored the interaction between diet diversity and viral infection in honeybees. Here, we used a mixture of laboratory cage and small semi-field nucleus hive experiments to determine how these factors interact. In laboratory experiments, we found that high-quality diets (polyfloral pollen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 63 publications
4
106
1
1
Order By: Relevance
“…Augmenting the amount and type of pollen can improve honey bee immunity to pathogens ( Parrinello et al 2011 , Foley et al 2012 , Di Pasquale et al 2013 ). When provided a diet composed of pollen from diverse plants or from a single plant that produces high-quality pollen, honey bee survival was improved when infected with Nosema parasite and lethal viruses ( Di Pasquale et al 2013 , Dolezal et al 2019b ). However, a diet of pollen from a single plant species of low-nutritional quality did not rescue bees from Nosema infection ( Di Pasquale et al 2013 ).…”
mentioning
confidence: 99%
“…Augmenting the amount and type of pollen can improve honey bee immunity to pathogens ( Parrinello et al 2011 , Foley et al 2012 , Di Pasquale et al 2013 ). When provided a diet composed of pollen from diverse plants or from a single plant that produces high-quality pollen, honey bee survival was improved when infected with Nosema parasite and lethal viruses ( Di Pasquale et al 2013 , Dolezal et al 2019b ). However, a diet of pollen from a single plant species of low-nutritional quality did not rescue bees from Nosema infection ( Di Pasquale et al 2013 ).…”
mentioning
confidence: 99%
“…Pollen is a critical component of the bee diet, affecting many aspects of bee biology [ 68 ], including immunocompetence [ 12 ], pesticide tolerance [ 26 ], and response to virus infection. Dolezal et al [ 13 ] showed that even the quality of pollen can influence mortality rates of bees infected with viruses. The exclusion of dietary pollen, therefore, prevents the accidental masking or augmentation of any potential effects incurred by phytochemical consumption, an observation that was shared by Palmer-Young et al [ 22 ] when discussing the effects of phytochemicals on pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
“…Dead bees were given priority over live bees for sampling to minimize depopulating the cages. The 36-hpi timepoint was selected as past experimentation has shown that this tends to be the point at which IAPV titers are highest within the bee without inducing lethal effects [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional status is among the most important modifiable determinants of honey bee health. In honey bees, malnutrition interacts with and amplifies the detrimental effects of parasites, pathogens, and pesticide exposure (Dolezal & Toth, 2018; Dolezal et al, 2019; Tosi, Nieh, Sgolastra, Cabbri, & Medrzycki, 2017). Pollen is the colony's main source of proteins, lipids, vitamins and minerals (Brodschneider & Crailsheim, 2010).…”
Section: Introductionmentioning
confidence: 99%